Kebisingan di Kapal KN Parajapati - Andi Hendrawan (Majalah Ilmiah Bahari Jogja, 2020)
High-intensity noise that is not realized causes serious impacts on the crew and inconvenience for each worker . Examples of noise that directly affects worker comfort include the main engine itself which is the biggest source of noise, exhaust gas outlets on the deck and auxiliary machinery and others. The purpose of this study was to determine the noise at every place on the KN Prajapati ship, the method used was direct measurement on the research object. The results of ship noise ranged from 50 to 65 dB are still below the permitted IMO of 65 dB and Government Regulation of 60 dB, indicating that noise is still the threshold allowed by IMO and the government.